2009
DOI: 10.1080/09540250902785905
|View full text |Cite
|
Sign up to set email alerts
|

‘Should you turn this into a complete gender matter?’ Gender mainstreaming in medical education

Abstract: The incorporation of a gender perspective in medical education aims toward better health, gender equity, and a better health care for both men and women. In this article, participants' responses to a Dutch gender awareness-raising project in medical education are discussed. Eighteen semi-structured interviews were held with education directors and change agents. Resistance towards and obstacles for gender mainstreaming in medical education were implicit in four themes: (1) biomedical knowledge was perceived to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 26 publications
0
33
0
11
Order By: Relevance
“…Reports from such implementation efforts describe the hard work required to inform and interest teachers. 3,[39][40][41][42] One obstacle is that gender issues seem to be considered to represent women's issues. Studies carried out in the USA 43 and Canada 44 showed that female medical faculty staff were more gender-sensitive and found gender discrimination to be more of a problem than men did.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Reports from such implementation efforts describe the hard work required to inform and interest teachers. 3,[39][40][41][42] One obstacle is that gender issues seem to be considered to represent women's issues. Studies carried out in the USA 43 and Canada 44 showed that female medical faculty staff were more gender-sensitive and found gender discrimination to be more of a problem than men did.…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, the way gender‐related issues are discussed can cause irritation. The project leaders of a Dutch programme designed to mainstream gender‐related issues were urged to communicate carefully to avoid resistance 42 . However, focusing on form more substantially than on content is a way of disregarding and downgrading an issue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations